2017
DOI: 10.1002/j.1681-4835.2017.tb00584.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mobile Phone Use and IKSL's Audio Messages on the Asset Base of Poor Farmers in Lucknow, India

Abstract: Mobile phones have the potential to improve the lives of poor farmers, in particular in combination with specifically designed mobile phone-based services (m-services) that provide agricultural information. Most impact studies have measured the economic effects of mobile phones, while disregarding how these effects have come about. Therefore, this study takes a qualitative approach in order to discover the various ways in which poor farmers' livelihoods are influenced by mobile phone use. A case study is based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…There are many ways in which mobile phones influence entrepreneurship. Evidence emerging from micro-level studies tends to support the conjecture that mobile phones improve market efficiency (Salia, Nsowah-Nuamah, & Steel, 2011;Lee and Bellemare, 2013), leads to higher incomes for small-scale entrepreneurs (Aker, 2010;Jensen, 2007), and improves social capital (Baardewijk, 2017), quality standards for buyers, and new opportunities for financial institutions (Qiang et al, 2012). Mobile ownership has been associated with better producer prices (Lee & Bellemare, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There are many ways in which mobile phones influence entrepreneurship. Evidence emerging from micro-level studies tends to support the conjecture that mobile phones improve market efficiency (Salia, Nsowah-Nuamah, & Steel, 2011;Lee and Bellemare, 2013), leads to higher incomes for small-scale entrepreneurs (Aker, 2010;Jensen, 2007), and improves social capital (Baardewijk, 2017), quality standards for buyers, and new opportunities for financial institutions (Qiang et al, 2012). Mobile ownership has been associated with better producer prices (Lee & Bellemare, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The social benefits of mobile phones have been linked to social inclusion and poverty reduction (Anwar & Johanson, 2015;Baardewijk, 2017;Beuermann, McKelvey, & Vakis, 2012). In Peru, it was found that household real consumption increased by 11%, poverty incidence fell by 8%, and extreme poverty reduced by 5.4% due to mobile phone adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…ICT have assumed the key part in the process of agrarian KM particularly in extension service delivery [14] and have demonstrated its value through the diverse small scale projects [12] that utilizes different strategies and procedures. ICT improves knowledge sharing by bringing down temporal [15]- [17] and spatial hindrances between knowledge specialists [15] and enhances access to information about knowledge [15], [16]. It upgrades the dissemination of explicit and tacit knowledge [18], and it enhances food security [19].…”
Section: B Related Workmentioning
confidence: 99%
“…A chance to give specialists new data gathering devices and alternative sources of information to augment or, at times, give alternatives to more conventional data-collection methods [30]. A chance to fortify social network [16], [31] allowing agriculturists to share their knowledge from their exploratory outcome [32]. Besides, the utilization of cell phones have demonstrated its value in the agrarian sector; it has likewise been helpful in healthcare service delivery [33], [34], governance [35], education [36], [37] and human development as a whole [38].…”
Section: B Related Workmentioning
confidence: 99%